Protective effect of astaxanthin on acute cerebral infarction in rats. (September 2018) - Nai, Yu; Liu, Hong; Bi, Xizhuang; Gao, Hongyu; Ren, Chao
The aim of the study was to investigate the effect of astaxanthin and its possible mechanisms on acute cerebral infarction (ACI) in rat model. Male Sprague Dawley rats were randomly divided into sham group, model group, and astaxanthin-treated groups (20, 40, and 80 mg/kg). Neurological examination, the ratio of cerebral edema, and histopathology changes were assessed. Moreover, some oxidative stress markers were obtained for biochemical analysis, and the expression of neurotrophic factors gene was detected by real-time polymerase chain reaction (RT-PCR) method. The results showed that treatment with astaxanthin notably reduced neurological deficit scores and the ratio of cerebral edema compared with the model group. Meanwhile, astaxanthin increased the activity of catalase, superoxide dismutase, and glutathioneperoxidase as well as decreased the content of malondialdehyde in brain tissue. RT-PCR results showed that the expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) mRNA were increased with astaxanthin treatment. The results indicated that astaxanthin could ameliorate ACI followed by suppressing oxidative stress and upregulating the expression of BDNF and NGF mRNA.